2009
DOI: 10.1002/msj.20087
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Fibrosing Diffuse Parenchymal Lung Disease

Abstract: The interstitial lung diseases are a heterogeneous group of disorders characterized by inflammation and/or fibrosis of the pulmonary interstitium. In 2002, the American Thoracic Society and the European Respiratory Society revised the classification of interstitial lung diseases and introduced the term diffuse parenchymal lung disease. The idiopathic interstitial pneumonias are a subtype of diffuse parenchymal lung disease. The idiopathic interstitial pneumonias are subdivided into usual interstitial pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 168 publications
0
27
0
4
Order By: Relevance
“…Studies from our laboratory suggest that the serine protease thrombin contributes to the development of SSc-ILD by activation of microvascular endothelial cells and by inducing the differentiation of lung fibroblasts to myofibroblasts [6,[19][20][21]. In the early stages of SSc-ILD we observed that the formation of new vessels occurs and coincides with the appearance of myofibroblasts [22]. These results suggest an interaction of endothelial cells with myofibroblasts, which may be crucial in the development of pulmonary fibrosis as seen in SSc-ILD and other ILDs.…”
Section: Discussionmentioning
confidence: 73%
“…Studies from our laboratory suggest that the serine protease thrombin contributes to the development of SSc-ILD by activation of microvascular endothelial cells and by inducing the differentiation of lung fibroblasts to myofibroblasts [6,[19][20][21]. In the early stages of SSc-ILD we observed that the formation of new vessels occurs and coincides with the appearance of myofibroblasts [22]. These results suggest an interaction of endothelial cells with myofibroblasts, which may be crucial in the development of pulmonary fibrosis as seen in SSc-ILD and other ILDs.…”
Section: Discussionmentioning
confidence: 73%
“…PF is a well known complication in a number of autoimmune diseases (Morgenthau and Padilla 2009). The prognosis in these patients depends on several factors like histology, baseline lung function, presence of autoantibodies and its titer level (Morgenthau and Padilla 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis in these patients depends on several factors like histology, baseline lung function, presence of autoantibodies and its titer level (Morgenthau and Padilla 2009). This is worse in overlap syndromes (Cambridge et al 1994;Derrett-Smith et al 2013;Szücs et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations